2020
DOI: 10.1097/ijg.0000000000001669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraocular Pressure on Aerosol Density Generated by Noncontact Tonometer Measurement

Abstract: Precis: Aerosols generated by a noncontact tonometer (NCT) were quantified. There was a positive correlation between aerosols and intraocular pressure (IOP), and the concentration of aerosols beside the air jet port was the highest. Purpose: To investigate the effects of IOP on the aerosol density generated during the use of an NCT and provide references and suggestions for daily protection of ophthalmic medical staff during the coronavirus disease-19 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…A previous study claimed that the IOP level might affect the concentration of generated aerosols. 13 As the binocular IOP difference was insignificant in our subjects, the PM concentration we recorded after NCT measurement of both eyes would not be affected. Our result indicated the local accumulation of aerosol on the lateral side of NCT, which can be applied to both eyes.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A previous study claimed that the IOP level might affect the concentration of generated aerosols. 13 As the binocular IOP difference was insignificant in our subjects, the PM concentration we recorded after NCT measurement of both eyes would not be affected. Our result indicated the local accumulation of aerosol on the lateral side of NCT, which can be applied to both eyes.…”
Section: Discussionmentioning
confidence: 66%
“…The accuracy and intra-model variability of such device has been presented by the Air Quality Sensor Performance Evaluation Center (AQ-SPEC) program, 17,18 and the device was also applied in the previous studies. 13,14 It was detected by a built-in laser particulate sensor and numerically displayed in the form of PM concentration. The measuring range of PM concentration was 0-999 μg/m 3 with a resolution of 0.1 μg/m 3 .…”
Section: Interventions and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested the potential for aerosolization of the tear film with NCTs which would pose a risk with the clinical use of these devices during this pandemic with concern of possible viral load in the tears. 11 – 13 However, the instructions for caution have been controversial and other research groups have contradicted such findings, indicating that NCTs do not generate droplets unless eye drops are given prior to the examination. 14 , 15 Given the recent emergence of several COVID-19 mutations, which reportedly have a higher infectious rate, as well as increasing evidence that the major disease transmission route is airborne, it is timely to characterize the potential for droplet formation with these devices.…”
Section: Introductionmentioning
confidence: 99%
“…16 Many studies have shown good correlation of CCT readings between USP and anterior segment optical coherence tomography (AS-OCT) regardless of the corneal thickness; [17][18][19][20] therefore, researchers tend to use noncontact methods. 16 Moreover, the transmissibility of the Coronavirus disease 2019 (COVID-19) from the ocular surface remains indefinite; thus, contact and aerosol-generating procedures are best avoided to prevent transmission, particularly among eyes with high IOP 21 and high tear volume. 22 Thin CCT underestimates IOP, while thick CCT overestimates IOP.…”
Section: Introductionmentioning
confidence: 99%